Employee Growth Mindset and Innovative Behavior: The Roles of Employee Strengths Use and Strengths-Based Leadership - Liu, Qiang; Tong, Yuqiong (Frontiers in Psychology, 2022)
This study aimed to investigate the relationship of employee growth mindset with innovative behavior and the mediating role of use of strength as well as the moderating role of strengths-based leadership in this relationship. Data with a sample of 244 employees working in diverse Chinese organizations were collected at two points in time. Results of bootstrapping analyses demonstrated that growth mindset is positively related to innovative behavior, employee strengths use partially mediates the positive relationship of growth mindset with innovative behavior, and strengths-based leadership strengthens the direct relationship between employee growth mindset and innovative behavior and the indirect relationship of employee growth mindset with innovative behavior via strengths use. This study advances growth mindset and innovative behavior theories and research.